Metacognition And Educational Achievement - Tolipova Gulfiya Fayzulla qizi; Khakimova Khosiyat Jurayevna; Axmedova Feruza Jabborali qizi (Euro Asian Journal Publishing, 2024)
The theme "Metacognition and Educational Achievement" explores the profound impact of metacognitive processes on academic success. Metacognition, involving the awareness and regulation of one's own cognitive processes, has emerged as a critical factor in shaping learning outcomes and overall educational achievement. This theme delves into various aspects of metacognition, such as goal setting, strategic planning, task monitoring, and evaluation, highlighting its influence on problem-solving skills and adaptive learning strategies. It underscores the link between metacognition and selfregulation, motivation, and the awareness of diverse learning styles. The theme also discusses the role of metacognition in facilitating the transfer of knowledge across different contexts and reducing cognitive load for more effective learning. Ultimately, the exploration of "Metacognition and Educational Achievement" emphasizes its practical implications for educators, encouraging the integration of metacognitive strategies into teaching practices to enhance students' cognitive awareness, self-directed learning, and overall academic success
Keywords: Cognitive processes; learning outcomes; academic performance